RUSSIAN-SAUDIAN POLITICAL INTERACTION - G. G. Kosach; E. S. Melkumyan; A. O. Filonik (Vestnik MGIMO-Universiteta)
The article analyzes the development of Russian-Saudi political interaction after the restoration (at that time of Soviet-Saudi relations) of bilateral relations in September 1990. The article focuses on the role of the Russian Muslim community in shaping the Russian politics towards Riyadh in the 1990-2000s. The authors state there are both periods of “crises” and detente in the development of Russian-Saudi political interaction that were marked by events in Chechnya and former Yugoslavia in 1994-2000, “Arab Spring” 2011, the post-September 2015 era, the Russian anti-terrorist campaign in Syria. The alternation of these periods is the constant of Russian-Saudi political contacts, despite the similarity in the approaches of both sides to the ways and methods of solving crisis situations in the Middle East region, as well as the Saudi’s pro-Russian position regarding the change in the status of the Crimea and the situation in the east of Ukraine. The general attitude of both sides towards ISIS and Jabha al-Nusra as a source of terrorism, regional instability and the challenge of international security does not remove the two main contradictions that divide Moscow and Riyadh – attitude toward the official Syrian regime and the Iran’s regional policy. The study comes to the conclusion that Russia and Saudi Arabia are interested (albeit for various reasons) in diversifying their foreign policy and foreign economic relations.